Thanks to Referees 2020/2021 - JSSE , Editors of the (JSSE - Journal of Social Science Education, 2022)
Maintaining the high quality of the Journal of Social Science Education is greatly dependent on the dedicated work of the academics who give their valuable time to review the papers that have been submitted to the journal. In the JSSE we are aware of the pressure for time that researchers have to face, and we are extremely grateful for their support to our editorial work. Thus the Editors of the Journal of Social Science Education would like to express our warm and heartfelt thank you to the following people who have reviewed papers for the journal in 2020 and 2021!